STATE OF THE SPECIFIC COMPONENT OF IMMUNITY IN CHILDREN WITH HYPOTROPHY - K.I. ISMOILOV; S.A. RASULOVA (Avicenna Tajik State Medical University, 2017)
Objective: The study of the state of the cellular component of immunity in children with hypotrophy Methods: The results of the study of 84 children aged 2 months to 2 years with hypotrophy, which were divided into 3 groups, depending on the mass deficit by Z-score index are presented. The state of the cellular component of the immune system was studied in all children. Results: The study of cellular immunity showed that in children of the group I of T-lymphocytes and their subpopulation (CD3, CD4, CD8, CD25, CD4, CD8, CD20, CD25, CD95 and CD16) were not significantly different from normal, but tended to reduction, especially the number of lymphocytes with CD4 immunophenotypes. In patients with moderate-to-severe hypotrophy (group II), a marked decrease in the average T-lymphocyte counts with immunological markers (CD4, CD8, CD16) was found in comparison with the similar indices of group I (p<0.001). In the group of patients with severe hypotrophy (group III), all indicators (CD4, CD8, CD16) and their subpopulations were significantly reduced in comparison with the group I (p<0.001). In comparison, the average of the T-lymphocyte counts with the CD4, CD8 and CD16 receptors in patients of the III groups correspond to indices of children with the mild and medium-weight hypotrophy with the statistically reliable difference (p<0.001). Conclusion: In children with hypotrophy, as the severity of the disease worsens, a secondary immunodeficiency state develops, the asynchronous decrease in the cellular component of immunity, which dictates the use of drugs in the complex treatment of immunodeficiency to this category of children.